Influenza. Issue 10353 (27th August 2022) - Uyeki, Timothy M; Hui, David S; Zambon, Maria; Wentworth, David E; Monto, Arnold S
Summary: Annual seasonal influenza epidemics of variable severity caused by influenza A and B virus infections result in substantial disease burden worldwide. Seasonal influenza virus circulation declined markedly in 2020–21 after SARS-CoV-2 emerged but increased in 2021–22. Most people with influenza have abrupt onset of respiratory symptoms and myalgia with or without fever and recover within 1 week, but some can experience severe or fatal complications. Prevention is primarily by annual influenza vaccination, with efforts underway to develop new vaccines with improved effectiveness. Sporadic zoonotic infections with novel influenza A viruses of avian or swine origin continue to pose pandemic threats. In this Seminar, we discuss updates of key influenza issues for clinicians, in particular epidemiology, virology, and pathogenesis, diagnostic testing including multiplex assays that detect influenza viruses and SARS-CoV-2, complications, antiviral treatment, influenza vaccines, infection prevention, and non-pharmaceutical interventions, and highlight gaps in clinical management and priorities for clinical research.